Knowledge-based information systems in practice - Tweedale, Jeffrey W. (Jeffrey Wayne).; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book contains innovative research from leading researchers who presented their work at the 17th International Conference on Knowledge-Based and Intelligent Information and Engineering Systems, KES 2013, held in Kitakyusha, Japan, in September 2013. The conference provided a competitive field of 236 contributors, from which 38 authors expanded their contributions and only 21 published. A plethora of techniques and innovative applications are represented within this volume. The chapters are organized using four themes. These topics include: data mining, knowledge management, advanced information processes and system modelling applications. Each topic contains multiple contributions and many offer case studies or innovative examples. Anyone that wants to work with information repositories or process knowledge should consider reading one or more chapters focused on their technique of choice. They may also benefit from reading other chapters to assess if an alternative technique represents a more suitable approach. This book will benefit anyone already working with Knowledge-Based or Intelligent Information Systems, however is suitable for students and researchers seeking to learn more about modern Artificial Intelligence techniques.
Electronic reproduction.
Keywords: Expert systems (Computer science); Artificial intelligence; Electronic books